In the spaces of exhibition history : a study of art exhibitions in Singapore from the 1970s to the 1990s - Hera (Nanyang Technological University, 2020)
This research is a study of art exhibitions in Singapore from the 1970s to the 1990s, focusing on the exhibition space as a source of discourses. Within an art exhibition, the disposition of space is fundamental in experiencing artworks, yet it is seldom given ample emphasis in writings on art. In response this project explores interdisciplinary methods to study the spaces of modern and contemporary art exhibitions, at the same time critically evaluating the concepts of space as a subject of historical study. This thesis consists of a two-part investigation: firstly, an overview study of the historical impulses and transformation of art exhibition spaces in the selected period and place; secondly a closer grained study of three selected case study exhibitions, using archival materials, interviews and developing the use of drawing as a research tool. Within the 1970s to the 1990s there was a significant change in terms of the typology of exhibition venues as well as the spatial articulations of artworks in exhibitions. These are symptomatic of the shifting ideologies of art amongst artists and stakeholders, as well as developments in Singapore’s policies and infrastructures. The changes also coincide with the transition between modern to the contemporary in Singapore’s art historical context, making the 1970s to the 1990s a pertinent period of study.